2011
DOI: 10.3389/fnsys.2011.00062
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Coding for Molecular Properties in the Olfactory Bulb

Abstract: The relationship between molecular properties of odorants and neural activities is arguably one of the most important issues in olfaction and the rules governing this relationship are still not clear. In the olfactory bulb (OB), glomeruli relay olfactory information to second-order neurons which in turn project to cortical areas. We investigate relevance of odorant properties, spatial localization of glomerular coding sites, and size of coding zones in a dataset of [14C] 2-deoxyglucose images of glomeruli over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…We found a good representation of our data with nine bulb regions, called modules. These modules show some analogy to previously reported regional structures in the bulb [5] [6]. Furthermore, we demonstrate a linkage between typical odorant characteristics and our modules, so this speaks in favour of a chemotopic coding map in the bulb.…”
supporting
confidence: 51%
“…We found a good representation of our data with nine bulb regions, called modules. These modules show some analogy to previously reported regional structures in the bulb [5] [6]. Furthermore, we demonstrate a linkage between typical odorant characteristics and our modules, so this speaks in favour of a chemotopic coding map in the bulb.…”
supporting
confidence: 51%
“…Our results from a systematic largescale study of glomerular activity indicated that coding of some molecular properties, including functional groups and chemical bonds, is organized in continuous zones and locally restricted (Auffarth et al, 2011a). Furthermore, the relative spatial locations between representational areas corresponding to odorant categories could be related to chemical similarity Ma et al, 2012;Auffarth et al, 2011a;Johnson et al, 2004).…”
Section: Physiologymentioning
confidence: 99%
“…Auffarth et al, 2011a;Matsumoto et al, 2010). It therefore seems plausible that lateral processing in the olfactory system makes use of a topographic organization.…”
Section: Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is now accumulating of behavioral relevance of molecular feature combinations and glomerular domains (e.g., Dielenberg and McGregor, 2001; Kobayakawa et al, 2007; Raman and Gutierrez-Osuna, 2009; Sakano, 2010). It has also been shown that perceptual differences can be predicted by glomerular spatial activity patterns (Uchida et al, 2000; Linster et al, 2001; Auffarth et al, 2011a). …”
Section: Introductionmentioning
confidence: 99%